Balance of design: exploring the harmony of conservation and development in landscape architecture - Sharp, Suzanne (Kansas State University, 2023)
Loss of natural land in the tallgrass prairie ecoregion due to urbanization and agriculture has been a significant issue in the last two hundred years. While the ecology and benefits of tallgrass prairie have been studied, it is vital to understand that development will not stop, and landscape architecture must help communities and regions address the balance of growth, housing, and preservation. This study explores this issue by examining conservation development and co-housing as two residential development models that can help preserve land. This study first examines three conservation developments and three co-housing communities to analyze themes in these communities and assesses their ecological and social benefits. The second method used is a projective design that applies the themes of conservation development co-housing to create a master plan of a site in the Flint Hills. This study finds that combining co-housing and conservation development can preserve the most land while creating socially beneficial communities. These findings can be used to influence future residential developments while still protecting natural landscapes and ecosystems.
Keywords: Landscape architecture; Conservation; Development; Cohousing; Conservation development